Examining the Applicability of Effective Operations Framework and Management in the Smart City Movement and Infrastructure Development - Amalraj, David (Digital Repository of Theses, 2026)
The high-speed urbanisation process and technological advances have enhanced the speed of smart city developments that aim at enhancing the sustainability of cities, infrastructures, and quality of life by incorporating digital technologies and data-oriented governance. However, without effective operations management frameworks, which would have the capacity to coordinate the movements of the different stakeholders, complicated systems of infrastructure, and informed decision making, the implementation of smart city programmes would be a failure. The objective of the study is to determine the role of operations management structure in efficient infrastructure management, stakeholder coordination, and integration of technology in smart cities. The current study seeks at identifying certain factors of operation, which define the success of smart city projects and overcome the challenges arising in the implementation of such projects. A qualitative research design was selected to emerge with a more profound understanding of the operating practices in the smart city endeavors. The data was obtained through interviews held as semi-structured ones with a total of nineteen individuals who were more directly involved in planning, managing, or implementing smart city programmes. The method through which the data was analysed was the thematic analysis, and therefore, discovered identical themes and trends with respect to governance, technology integration, and operations coordination. The findings of the study indicate that well-functioning operations management systems have the potential to significantly enhance stakeholders' alignment, the management system of infrastructure, and make smart decisions in smart city endeavors. These results highlight some of the most important success areas, which include the integrated data management systems, collaborative governance structures, technological readiness, and a loose policy structure. At the same time, the problem of data interoperability, institutional disaggregation, and technical deficiencies were witnessed as the barriers to effective implementation. The study adds to the knowledge of smart city governance and infrastructure management since it reveals how properly organized operation systems are used as a tool to realize sustainable city development. The results can be used to offer practical information to policymakers, urban planners, and infrastructural managers who would like to make the smart cities projects more efficient, tolerable, and sustainable.